The Influence of Learning Models and Motivation Study On Learning Outcomes Student Class V of Elementary School 106 Pekanbaru - Nurul Intan Supradilla; Damrah Damrah; Arsil Arsil; Yuni Astuti (STKIP Singkawang, 2025)
Problem in study This low results study students and lack of motivation Study student class V Elementary School 106 Pekanbaru . Research This aiming For to reveal The influence of the STAD training model , Inquiry and motivation Study to results learning physical education for students at State Elementary School 106 Pekanbaru. Research methods is use quasi- experimental method which use design treatment by Level 2 x 2 , namely a factorial experiment involving two factors . Research sample This is student class V of Elementary School 106 Pekanbaru, totaling 32 people . Motivation Study student measured use questionnaire and for results Study use mark eye Physical Education lessons . Data analyzed using two -way ANOVA at the level significance α=0.05 and normality test Shapiro-Wilk Sig. > 0.05 and continued with Tukey's test. The results of the data analysis show that : (1) In overall there is difference results learning Physical education, sports and health between the STAD learning model and the learning model inquiry (2) There is interaction between learning models and motivation Study to results learning Physical education, sports and health (3) In groups that have motivation Study the STAD learning model is higher Good than learning models inquiry (4) In groups that have motivation low STAD learning model does not more Good than learning models inquiry.